Diversity of Coral-Associated Fauna (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Coral reefs are acknowledged for the beauty of their organisms, which has made this natural ecosystem one of the most appreciated on Earth. It is believed to be the richest in terms of species diversity and species interactions, at least in theory since there is yet much documentation work to be done. Indeed, the paradox is that of the estimated one million species living in this ecosystem globally, only 10% of them have been described. To date, most of the coral reef studies have focused on the most peculiar and fabulous groups, such as corals and fishes, although most of the diversity is usually represented by small, colored, camouflaged, hidden, and crypto organisms from all kingdoms of life. The mystery of their diversity, ecology, biology, and importance in the functioning of coral reefs motivate many scientists to dive, all around the world, in order to discover, name, and appreciate such a fascinating, but unfortunately overlooked, component of nature. This book is a very nice illustration of the charm of the coral-associated fauna.